?CYSTIC ECHINOCOCCOSIS IN DOMESTIC RUMINANTS IN COX’S BAZAR OF BANGLADESH - Islam, M K; Basakb, S C; Majumder, S; Sarderd, S A; Islam, A W M S; Mondal, M M H (Biological Sciences - PJSIR, 2003)
This investigation was carried out to describe the local epidemiological pattern of cystic echinococcosis among the indigenous domestic ruminants in the Cox’s Bazar district of Bangladesh. Home visits and family interviews revealed several socio-economic and cultural characteristics which are thought to be involved in the transmission cycle and widespread occurrence of cystic echinococcosis in the area. Fecal examination of stray and house dogs showed high infection levels (50.65%) with Echinococcus granulosus. A significantly higher (p < 0.00) prevalence of cystic echinococcosis was recorded in sheep (52.11%) than buffaloes (36.11%), cattle (30.62%) and goats (14.73%). The values of chi-square test and regression-coefficient analysis strongly indicate that age is an important risk factor of being higher infestation with cystic echinococcosis. While sex had no influence on the prevalence of the disease. Lungs of all ruminant hosts were the most common predilection site for Echinococcus cysts, liver ranked second, followed by spleen, kidneys and heart. Fertility rate of the cysts was recorded high in sheep (65.43%) than buffaloes (16.33%), goats (14.80%) and cattle (8.11%). The high level of infection with cystic echinococcosis in domestic ruminants and dogs suggests that there is an urgent need for control measure against the disease in the Cox’s Bazar area.